Environmental Encyclopedia - Bortman, Marci (Macmillan Reference USA, 2011)
Consisting of nearly 1,300 signed articles and term definitions, the 3rd edition of the award-winning Encyclopedia provides in-depth, worldwide coverage of environmental issues. Each article is written in a nontechnical style and provides current status, analysis and suggests solutions whenever possible.